Anatomical variations of circle of Willis - a cadaveric study - Singh, Ramanuj; Kannabathula, Ajay Babu; Sunam, Himadri; Deka, Debajani (International Surgery Journal, 2017)
Background: The circle of Willis (CW) is a vascular network formed at the base of skull in the interpeduncular fossa. Its anterior part is formed by the anterior cerebral artery, from either side. Anterior communicating artery connects the right and left anterior cerebral arteries. Posteriorly, the basilar artery divides into right and left posterior cerebral arteries and each join to ipsilateral internal carotid artery through a posterior communicating artery. Anterior communicating artery and posterior communicating arteries are important component of circle of Willis, acts as collateral channel to stabilize blood flow. In the present study, anatomical variations in the circle of Willis were noted. Methods: 75 apparently normal formalin fixed brain specimens were collected from human cadavers. 55 Normal anatomical pattern and 20 variations of circle of Willis were studied. The Circles of Willis arteries were then colored, photographed, numbered and the abnormalities, if any, were noted. Results: Twenty variations were noted. The most common variation observed is in the anterior communicating artery followed by some other variations like the Posterior communicating arteries, Anterior cerebral artery and posterior cerebral artery (PCA) was found in 20 specimens. Conclusions: Knowledge on of variations in the formation of Circle of Willis, all surgical interventions should be preceded by angiography. Awareness of these anatomical variations is important in the neurovascular procedures.